Analysis Of Milk Consumption Behavior and Processed Products on IPB Students with AIDA and CRI Methods - Widaryanti, Widya Bella; Retnaningsih, Retnaningsih (Journal of Consumer Sciences, 2018)
This study aimed to analyze consumption behavior of Fapet’s milk and processed products using the AIDA and CRI models. Samples in this study were 209 active students of IPB in 2nd, 4th, and 6th semester used simple random sampling method. The results showed that there was a correlation between awareness and interest, interest and desire, while desire has no correlation with action. The results also showed that sex, pocket money, father’s occupation, number of family member, awareness, interest, and action have a correlation with consumption frequency of Fapet’s milk and processed products. Awarenes, interest, and action variables also have a correlation with consumption quantity of Fapet’s milk and processed products. The enhancement of awareness and action will increase consumption frequency and consumption quantity of Fapet’s milk and processed products. Results of Customer Response Index (CRI) analysis showed that students response to dairy Fapet milk and processed products were 78.9 percent indicating that marketing strategy have been effective.